Word Boundary Detection in Assamese Language - Sarma, Sudarshana; Sharma, Uzzal (International Journal of Computer Sciences and Engineering, 2015)
Detection of word boundary in continuous speech is an important issue in speech recognition. This paper presents different methods for detecting word boundary in Assamese language and also discusses the possible future development to improve the accuracy. These methods are based on the behavior of pitch frequency across the sentences. Here we use Scilab, Praat and Wavesurfer software.